MODUL KETERAMPILAN BINA DIRI ANAK RETARDASI MENTAL - Tyas Leylasari, Herdina (Widya Warta, 2019)
This research aimed to create a development module of a child with mental retardation for teachers and parents. This is a development research especially about a process or procedure to develop a new product. The data were collected in two steps, namely assessment and intervention. The assessment was done using interviews and observations. The intervention was conducted by applying evaluation on questionnaires concerning the module. Participants of this research were teachers and parents. The data analysis in the assessment made use of content analysis technique and the one in the intervention applied percentage calculation. The results of the assessment showed the problems experienced by teachers and parents in teaching self help skills. They were (a) less accurate assessment for seeing the competence of child with mental retardation, (b) insufficient supporting infrastructure, (c) less accurate learning curriculum, process, and evaluation. Likewise, the results of the intervention indicated that the module was quite helpful for the teachers and parents in teaching self-help skills.